On Best Proximity Points of Generalized Almost-F-Contraction Mappings - Hamlbarani Haghi, Robab; Salamatbakhsh, Mahdi (Journal of the Indonesian Mathematical Society, 2019)
We provide some results about best proximity points of generalized almost-$F$-contraction mappings in metric spaces which generalize and extend recentÂ  fixed point theorems. Also, we give an example to illustrateÂ  our main result.